Narrative and constructivism in cyberspace: Instructional design for distance delivery using hypertext on the internet - Nick Zepke (Flexible Learning Association of New Zealand, 2012)
This explores two aspects of instructional design in the delivery of distance using hypertext on the Internet. It first considers the role of narrative: a fixed sequence of learning experiences organised by the instructor. Secondly it examines the role of learners in constructing their knowledge by interacting with peers, teachers and diverse material on World Wide Web sites on the Internet. The paper concludes with a working model for designing distance education programmes using hypertext on the Internet.